Audit Delay Analysis to Support the Effectiveness of Company’s Financial Reporting on Manufacturing Companies Listed On The Indonesia Stock Exchange - Tjahjani Murdijaningsih; Siti Muntahanah (Universitas Batanghari, 2021)
Every company listed on the Indonesia Stock Exchange is required to submit financial reports periodically. The financial statements shall be submitted no later than the end of the third month from the end date of the financial year. In reality, not all companies submit the right reports on time because of the audit reports, so that the company's financial reporting is not effective. Delays in financial reporting are closely related to audit delays. This study aims to analyze the factors that affect the time spent in auditing financial statements. The sample in this study were 15 real estate and property industrial companies listed on the Indonesia Stock Exchange for the period 2013-2017. Determination of the sample in this study using the purposive sapling method. The analysis used is multiple regression analysis. The results showed that company size had no significant effect on audit delay. Meanwhile, profitability has a negative effect and the size of the public accounting firm has a significant positive effect on audit delay. The size of the company cannot determine the audit of the financial statements to improve the accuracy of the submission of financial statements. What must be paid more attention is the level of profitability and the public accounting firm that will be used.